2017
DOI: 10.1097/htr.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Postural Impairments in Children With Mild Traumatic Brain Injury: Implications for Acute Testing

Abstract: Following mild traumatic brain injury, children acutely demonstrate significantly more rigid sway patterns with eyes closed than with eyes open, which were highlighted by the Romberg quotient. The Romberg quotient could allow for accurate identification and tracking of postural instability without requiring knowledge of preinjury balance ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…28 In addition, this plane has also been shown to be sensitive to time postconcussion in a pediatric hospital setting. 17 A similar pattern emerged on the individual level. Whereas the BESS and ImPACT were also sensitive to changes in balance and neurocognition, respectively, across the 3 time points, our individual-level analysis (Figure 2) showed that, at day 3 postconcussion, the WBB classified 1 athlete (participant 12) as nonrecovered who would have been classified as recovered by the BESS and ImPACT.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…28 In addition, this plane has also been shown to be sensitive to time postconcussion in a pediatric hospital setting. 17 A similar pattern emerged on the individual level. Whereas the BESS and ImPACT were also sensitive to changes in balance and neurocognition, respectively, across the 3 time points, our individual-level analysis (Figure 2) showed that, at day 3 postconcussion, the WBB classified 1 athlete (participant 12) as nonrecovered who would have been classified as recovered by the BESS and ImPACT.…”
Section: Discussionsupporting
confidence: 48%
“…13 Thus, the WBB may be a useful tool for assessing postconcussion balance impairments, given that force platforms have previously shown their utility. 11,14 However, few researchers have quantified postconcussion balance symptoms using a WBB, [15][16][17] and no studies have included prospective data, with preinjury and postconcussion balance assessments. Furthermore, given that cognitive testing is widely used in concussion management, we aimed to determine the extent to which the WBB measures provide additional information about concussion recovery that is not captured by cognitive testing.…”
mentioning
confidence: 99%
“…4 In mild pediatric TBI, postural instability has been noted one month after injury, 5 deficits in visual-motor response time and dynamic balance have been observed up to 12 weeks post-injury, 6,7 and dynamic balance issues and tremors have been reported for up to six months post-injury. 8 Additionally, in a cohort of children with mild to moderate TBI, even subtle motor deficits that were present two months post-injury had largely resolved by one year post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to motor sequelae, children with more severe injuries who require inpatient rehabilitation often experience marked motor deficits in fine motor control and strength and gross motor skills (e.g., balance and gait) which persist throughout and beyond the first year postinjury (Ahlander, Persson, & Emanuelson, 2013; Katz-Leurer, Rotem, Keren, & Meyer, 2010; Kuhtz-Buschbeck, Hoppe, et al, 2003). Conversely, in mild TBI literature behavior problems (Taylor et al, 2015) and cognitive issues (Loher, Fatzer, & Roebers, 2014) are typically studied, but motor deficits are also examined (Babikian et al, 2011; Gagnon, Swaine, Friedman, & Forget, 2004a, 2004b; Howell, Osternig, Koester, & Chou, 2014; Rhine, Quatman-Yates, & Clark, 2015; Wallen, Mackay, Duff, McCartney, & O’Flaherty, 2001). …”
mentioning
confidence: 99%
“…Babikian et al (2011) also found no deficits on pure motor speeded measures but when collapsing data collected one, six, and 12 months postinjury did observe small differences between children with mild TBI and uninjured controls on motor tasks with cognitive components (e.g., Color Trails). In subacute stages (i.e., 1–3 months postinjury) of mild TBI, multiple authors have identified gross motor deficits including postural instability (Rhine et al, 2015) and impaired dynamic balance (Gagnon et al, 2004a; Howell et al, 2014); longer term follow-up of these findings has not been reported, though in adults, motor findings have been identified years after mild TBI (Martini et al, 2011). In summary, following mild pediatric TBI, subtle motor deficits may be observed in the months postinjury, but less is known about the longitudinal course of these findings.…”
mentioning
confidence: 99%